4.0k views
2 votes
Factorise 9f²-12f plus 4​

User Apogee
by
4.6k points

2 Answers

5 votes

Answer:

(3f - 2)²

Explanation:

Given

9f² - 12f + 4

Consider the factors of the product of the coefficient of the f² term and the constant term which sum to give the coefficient of the f- term.

product = 9 × 4 = 36 and sum = - 12

The factors are - 6 and - 6

Use these factors to split the f- term

9f² - 6t - 6t + 4 ( factor the first/second and third/fourth terms )

= 3f(3f - 2) - 2(3f - 2) ← factor out (3f - 2) from each term

= (3f - 2)(3f - 2)

= (3f - 2)²

User Ramon Tayag
by
4.9k points
2 votes

Answer:

9f² - 12f + 4 = (3f - 2)²

Explanation:

9f²-12f+4 =

= (3f)²-2×(3f)×(2)+2²

= (3f-2)²

User Yasina
by
5.5k points